Ground Reaction Forces and Throwing Performance in Elite and Novice Players in Two Types of Handball Shot - Rousanoglou, Elissavet (Akademia Wychowania Fizycznego w Katowicach, 2014)
The purpose of this study was to examine the differences in the ground reaction force (GRF) patterns between elite and novice players during two types of handball shots, as well as the relationships between throwing performance and the GRF variables. Ball velocity and throwing accuracy were measured during jump shots and 3-step shots performed by 15 elite and 15 novice players. The GRF pattern was recorded for the vertical and the anterior-posterior GRF components (Kistler forceplate type-9281, 750Hz). One-way ANOVA was used for the group differences and the Pearson coefficient for the correlation between throwing performance and GRF variables (SPSS 21.0, p ≤ 0.05). The elite players performed better in both types of shot. Both groups developed consistent and similar GRF patterns, except for the novices’ inconsistent Fz pattern in the 3-step shot. The GRF variables differed significantly between groups in the 3-step shot (p ≤ 0.05). Significant correlations were found only for ball velocity and predominantly for the novice players during the 3-step shot (p ≤ 0.05). The results possibly highlight a shortage in the novice ability to effectively reduce their forward momentum so as to provide a stable base of support for the momentum transfer up the kinetic chain, a situation that may predispose athletes to injury.